2011
DOI: 10.1530/rep-11-0211
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone as a predictive endocrine marker for embryo production in the goat

Abstract: Recently, we demonstrated the relationship between anti-Mü llerian hormone (AMH) circulating concentrations, ovarian follicles, and embryo production in cattle. However, they have not yet been established in a species with a seasonal breeding activity. Thus, goats were subjected to repeated in vivo embryo production during the breeding season, at the end of the breeding season, and at the end of the anestrus season. Embryo production after FSH treatment was highly repeatable for each goat. Plasma AMH concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 51 publications
2
54
2
4
Order By: Relevance
“…Therefore, the response to FSH stimulation may slightly vary according to the phase of the follicular wave during which the gonadotropin stimulation occurs. However, AMH concentrations remain relatively constant along the whole cycle because there is a continuous growth of small follicles (La Marca et al 2007) following a specific profile during the estrous cycle which occurs independently of the follicular waves (Rico et al 2011); exhibit very little changes with season in seasonal breeding animals (goat, Monniaux et al 2011), and arepositively correlated to ovarian response to exogenous stimulation (TorresRovira et al 2014). Thus, we believe that the differences seen in the basal concentrations of AMH on Day 0 between the high and low AFC groups support the existence of the differences seen between both groups at 16.5 months in the EFORT response despite the nonsynchronization of the follicular wave.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the response to FSH stimulation may slightly vary according to the phase of the follicular wave during which the gonadotropin stimulation occurs. However, AMH concentrations remain relatively constant along the whole cycle because there is a continuous growth of small follicles (La Marca et al 2007) following a specific profile during the estrous cycle which occurs independently of the follicular waves (Rico et al 2011); exhibit very little changes with season in seasonal breeding animals (goat, Monniaux et al 2011), and arepositively correlated to ovarian response to exogenous stimulation (TorresRovira et al 2014). Thus, we believe that the differences seen in the basal concentrations of AMH on Day 0 between the high and low AFC groups support the existence of the differences seen between both groups at 16.5 months in the EFORT response despite the nonsynchronization of the follicular wave.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AMH concentrations before treatment were predictive of the response to superovulation in sheep (Lahoz et al 2014), goats (Monniaux et al 2011) and mares (Claes & Ball 2016). These findings confirm the positive association between the response to superovulation and the ovarian reserve and support the use of AMH assessment to select donors for embryo production.…”
Section: Superovulationmentioning
confidence: 99%
“…In contrast, information on the relationship between age and plasma AMH concentration in adult female ruminants is lacking, although one study [6] found a positive correlation between pregnancy rate and plasma AMH concentration in dairy cows. Furthermore, the concentration of circulating AMH can predict the number of high-quality embryos produced by a donor goat or cow [7, 8]. These data suggest that there must be an optimal blood AMH concentration for proper reproductive function in ruminants.…”
mentioning
confidence: 99%